Simulation model generation for warehouse management: case study to test different storage strategies. (2018) - Vieira, Antonio A.C.; Dias, Luís M.S.; Pereira, Guilherme A.B.; Oliveira, José A.; Carvalho, Maria Do Sameiro; Martins, Paulo
A simulation model generator was developed to help a company of the Bosch Group to reduce costs in time and space with its warehouse. The simulation models are automatically created in Simio and can simulate pickers riding milk runs to collect containers from the warehouse, to satisfy the needs of production lines, assisting warehouse management by testing different storage strategies. Thus, the purpose of this paper is to present the developed generator and to use it in a case study, to test different storage policies for the company. The generator was validated, as was the simulation model automatically created. With this tool, some suggestions could be made to the company in question. Namely, it was shown that it would not be possible to maintain the FIFO rule and, at the same time, eliminate the upper floor of all racks for ergonomic reasons. To allow this, the rate of replacing containers should be synchronised with the needs of production lines. Alternatively, it was also shown that the performance of the warehouse would improve by dividing it into zones allocated to each milk run.